Diabetes mellitus and colorectal cancer screening in the population of the Italian region Friuli Venezia Giulia (Epidemiology, Biostatistics, and Public Health, 2022)
Aims: Colorectal cancer is the most common cancer in Italy, where screening programs are now in place all over the country. We conducted a research to assess whether the use and outcomes of colorectal cancer screening are different between diabetics, who are at increased risk of developing colorectal cancer, and non-diabetics in the Italian Northeastern region Friuli Venezia Giulia.Methods: This was a retrospective population-based study which used the administrative databases of the regional health information system as the sources of information. For the two screening rounds 2010-2011 and 2012-2013, we compared adherence to the program and the results of the fecal occult blood tests and of the colonoscopy among diabetic and non-diabetic residents.Results: Overall, more than 300,000 persons were invited for the colorectal cancer screening in each round. Of them, approximately 8.8% were diabetic. In the regional population, adherence to the screening program was significantly lower among diabetics than among non-diabetics. The proportion of positive fecal occult blood tests was higher among diabetics than among non-diabetics. Among diabetics, the detection rate for initial and advanced adenomas was higher than among non-diabetics, whereas no clear pattern was observed for the detection of cancers.Conclusion: In Friuli Venezia Giulia, efforts should be directed at improving the management of diabetic patients and at reducing the inequalities in access to care due to this comorbidity.